Constraints Mitigation in Cognitive Radio Networks Using Cloud Computing - V, Bindhu (Journal of Trends in Computer Science and Smart Technology, 2020)
One of the most supportive technologies in enhancing the bandwidth utilization of the next generation network is cognitive radio network (CR-N). However the traditional CR-N is substantially constrained in accessing and the spectrum sensing, due to its limited, processing power and the storage capabilities. To advance the spectrum sensing performance and the spectrum management along with the development in the radio frequency resource allocation in the CR-N the paper clouts the cloud computing services in the proposed method to mitigate the constraints in the cognitive radio networking and also address the intrinsic security threats that are caused by the jamming in the CR-N. The performance of the proposed method is validated and the results are observed to evince the performance enhancement gained in managing the constraint in the CR-N using the cloud.
Keywords: Cloud Computing; Vast Storage; Computational Capability; Cognitive Radio Network; Spectrum Sensing; Spectrum Management